Weaving pathways: talking with our Elders - Mary Owen; Peter Nalin; Charlie Bouverette; Ginearosa Carbone; Charles Neher; Elisabeth Pederson; Mangan Golden (James Cook University, 2022)
While there exists a relative paucity of completed healthcare directives nationally in the USA, even fewer exist within minority populations. This report describes one model for bringing advance care planning and discussions to American Indian and Alaska Native (AIAN) communities. In 2018, Honoring Choices of Minnesota approached the Center of American Indian and Minority Health (CAIMH), housed in the University of Minnesota Medical School, to collaborate on a project to increase healthcare directives in AIAN communities. CAIMH assembled AIAN students, faculty and community members to identify and address barriers to healthcare directive completion and discussions about end-of-life choices. The project team decided upon a two-pronged approach: culturally informed provider training paralleling culturally relevant community engagement. We aimed to empower AIAN to engage with healthcare providers on decisions impacting their care. To further support AIAN patients and their providers, a toolkit was created and will soon be available for dissemination.